2020
DOI: 10.1021/acs.analchem.9b05232
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of Protein Vicinal Dithiols in Parkinsonism Disclosed by a Monoarsenical Fluorescent Probe

Abstract: Vicinal dithiol-containing proteins (VDPs) play an important role in maintaining the structures and functions of proteins mainly through the conversion between dithiols and disulfide bonds. The content of VDPs also reflects the redox status of an organism. To specifically and expediently detect VDPs, we developed a turn-on monoarsenical fluorescent probe (NEP) based on the intramolecular charge transfer mechanism. Naphthalimide was chosen as a fluorophore and linked with the receptor moiety (cyclic dithiarsola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“… 143 , 144 Exofacial neighboring thiols have been imaged with such fluorescent arsonodithioite exchangers. 23 25 Phenyl arsine oxides were also shown early on to inhibit the entry of HIV virus about as efficiently as DTNB. 8 In clear contrast, thiol-mediated uptake and its inhibition remain a fascinating topic to be explored with dynamic covalent pnictogen chemistry, including possible contributions of turned-on noncovalent pnictogen bonds into deepened σ holes.…”
Section: Perspectivesmentioning
confidence: 99%
“… 143 , 144 Exofacial neighboring thiols have been imaged with such fluorescent arsonodithioite exchangers. 23 25 Phenyl arsine oxides were also shown early on to inhibit the entry of HIV virus about as efficiently as DTNB. 8 In clear contrast, thiol-mediated uptake and its inhibition remain a fascinating topic to be explored with dynamic covalent pnictogen chemistry, including possible contributions of turned-on noncovalent pnictogen bonds into deepened σ holes.…”
Section: Perspectivesmentioning
confidence: 99%
“…Gathering lines of evidences suggested that trivalent arsenicals interacted readily with vicinal dithiol-containing proteins. ,, TrxR has a C-terminal active site as the sequence of −Gly–Cys–Sec–Gly–COOH, and this spatially close thiol/selenol pair is exposed on the TrxR surface. Our previous study and the recent work by Zhang et at .…”
Section: Resultsmentioning
confidence: 75%
“…We also treated the cells with varying concentrations of H 2 O 2 , and a dose-dependent increase of the fluorescence signal was observed (Figure B). Zebrafishes have been widely used as a model vertebrate in biomedical research. We further demonstrated that the probe is readily applied to image PDS in zebrafishes (Figure C).…”
Section: Resultsmentioning
confidence: 87%